Perlindungan Pasar Tradisional Terhadap Dominasi Toko Swalayan Dalam Perspektif Hukum Persaingan Usaha - Ananda, Khairum Mahda Syahri; Fitriani, Rini; Fatimah (Legalita, 2025)
Abstract This study aims to analyze the application of competition law principles in protecting traditional markets from the domination practices carried out by supermarkets, based on Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. The research method employed is a normative juridical approach by examining the protection of traditional markets from the dominance of supermarkets through the principles of competition law. The findings indicate that the presence of supermarkets located near traditional markets creates structural imbalances in terms of prices, product quality, services, and facilities. This condition drives changes in consumer behavior and weakens the competitiveness of traditional traders, thereby showing indications of unfair business practices, particularly in the form of predatory pricing and abuse of dominant position. Therefore, the Langsa City Government needs to strengthen the implementation of zoning policies, revitalize traditional markets, and provide empowerment support to small traders. Through these measures, a balance between modern retail investment and the protection of the people’s economy is expected to be achieved, thus realizing the principles of fair, equitable, and healthy business competition.